Cyclic Behavior of New Steel Plate Shear Walls Reinforced with Trapezoidal Corrugated Plates - Dashti Zand, Seyedeh Maryam; Kalatjari, Vahidreza; Attari, Nader K. A. (Periodica Polytechnica Civil Engineering, 2024)
Unstiffened steel plate shear walls have low buckling strength, which caused development diagonal tension field under lateral load. Corrugated plates have higher out-of-plane stiffness and improved buckling stability. Combining corrugated and flat plates in steel shear wall web could be effective. In this paper a new steel shear wall system reinforced with trapezoidal corrugated steel plates were proposed. In this study, the behavior of the system was experimentally studied under cyclic loading. Four specimens with the one-third scale were evaluated, which were control unstiffened specimen, the specimen with vertical 45° trapezoidal corrugated web, specimen with a corrugated web plate reinforced with two flat plates, and specimen with a flat web plate reinforced with two corrugated plates. In all four specimens, the total thicknesses of steel plates were the same; therefore, the thickness of each plate in specimens with three plates was one-third of the specimen with one plate. The studied parameters were the bearing capacity, maximum base shear, stiffness, ductility, energy absorption, and modification factor for the dissipation capacity of the specimens. The results revealed the maximum lateral load capacity of specimen with a flat web plate reinforced with two corrugated plates increased about 17%, 37%, and 19%, comparly to unstiffened specimens, vertical 45° trapezoidal corrugated web, and corrugated web plate reinforced with two flat plates, respectively. According to the results, the behavior of the seismic parameters of the proposed specimen with a flat web plate reinforced with two corrugated plates was clearly better than that of the other specimens.